The impact of personality structure on outcomes of mediation - Ellison, Jennifer Anne (Curtin University, 2015)
The aim of this study was to investigate how personality disorders and defenses contribute to satisfaction with workplace mediation. The results found that higher scores on the MCMI-III for Cluster B (Dramatic-Emotional) and Cluster C (Anxious-Fearful) personalities and higher scores for Denial on the DSQ can be considered potential predictors of lower satisfaction with workplace mediation. These results provided a basis for research-based suggestions for mediators to manage personality factors in workplace mediation.